LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PT. BANK MANDIRI TBK. DAN ENTITAS ANAK - Herawati, Helmi (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2016)
Helmi Herawati; The bank's financial performance assessment is based on three types of the bank liquidity ratio, the bank's solvability ratio and bank profitability ratio. Competition between banks in collecting funds from the public and channel funds from the public in the form of loans by commercial banks will be more stringent. Competition among banks in practice many banks are less careful, or deviate from the rules that apply in the world of banking business. The research objective was to determine the financial performance of PT Bank Mandiri, Tbk and its subsidiaries based on financial ratios of the Bank. This type of research is a comparative study, based on three ratios mentioned above indicates PT Bank Mandiri, Tbk and its subsidiaries periods of 2013 and 2014 in good positionKeywords: Financial Statements, The Financial Performance Of The Bank's Financial Ratios